Wired Snare and Negus Artery Ligation for Securing Lower Pole Tonsillar Removal during Cold Steel Tonsillectomy: A Comparative Study - Fatah, Soran Mohammed Ali; Chalabi, Yousif Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Tonsillectomy is one of the most commonly practised surgeries in general and otolaryngology. Bleeding tonsillar lower pole, primarily pain and tonsillar remnant are common complications of this operation. Objectives: To assess and compare the effectiveness of wired snare removal of the inferior tonsillar pole with negus artery ligaturisation technique regarding bleeding, pain, operative time, and the tonsillar remnant in cold dissection tonsillectomy. Patients and Methods: This hospital-based, prospective, comparative study was conducted on 200 patients (400 tonsils) that underwent a tonsillectomy in Sulaimani Teaching Hospital and Shorsh Teaching Hospital from April 2021 to February 2022. On one side, the tonsil's inferior pole was removed by silk using negus artery ligaturisation, while the other lower pole tonsil of the same patient was crushed by wired eves snare. Patients followed up on the 4 th, 7th day, and 8th weeks postoperative for bleeding, pain, fever, and tonsillar remnant. Results: Most patients were aged 5-10 years (48.5%) and males (56%). The mean±SD of surgical time for wired snaring was significantly (p=0.000) shorter (6.04±0.47 minutes) than that of artery ligation (7.0±1.55 minutes). The tonsillar remnant occurred mainly with ligation, while bleeding more commonly occurred on the snare side (p=0.048). Conclusions: Lower tonsillar pole negus ligation removal was associated with less bleeding and pain. However, it is more time-consuming operatively, with more tonsillar remnant occurrence than wired snare removal of the lower pole.
Keywords: Tonsillectomy; complications; inferior lower pole snaring; negus ligaturisation; prospective study